Personal valuation and the quality of life of servers in the pedagogical coordination of a Federal Institute of Education, Science and Technology (Research, Society and Development, 2023)
The Pedagogical Coordination in Federal Institutes plays a crucial role in promoting and integrating students, teachers, and families, establishing healthy interpersonal relationships to enhance the teaching and learning process. This article aims to identify the causes of difficulties in the service provided by the Pedagogical Coordination at the Federal Institute of Santa Catarina, Joinville campus, focusing on human appreciation and quality of life for these employees. This qualitative bibliographic research also constitutes an applied case study, collecting data through questionnaires from twelve Pedagogical Coordination employees. The analysis of the state of knowledge and the organization of the questionnaire responses revealed the following aspects: a) the role of pedagogical coordination in the context of Federal Institutes; b) staff appreciation; c) profile of the participants in the research; d) quality of work life: employees' perception. The results indicated that recognizing each staff member's profile improves both the workplace conditions and the well-being of the employees. It was also observed that the current resolution flows of demands in the sector affect employee well-being during work hours. In conclusion, encouraging the personal appreciation of the Pedagogical Coordination staff within the context of professional education enhances sector productivity, reduces service difficulties, and improves the quality of work life for these professionals